ANALISIS GAYA BAHASA PERSONIFIKASI DALAM NOVEL SRIMENANTI KARYA JOKO PINURBO - Tajuddin, Devianti; Abbas, Asriani; Thaba, Aziz (VOKAL: Jurnal Ilmiah Bahasa dan Sastra Indonesia, 2023)
This study aims to describe the form of words used to construct personification language style in the novel Srimenanti by Joko Pinurbo. This type of research is descriptive qualitative. The source of data in this study is the novel Srimenanti by Joko Pinurbo published by PT Gramedia Pustaka Utama, Jakarta, in 2019. The technique used in analyzing this study is the personification style analysis technique to determine novel language style based on stylistic theory. The results showed that (1) there are three types of prefixes used in constructing personification language styles, namely: the use of the prefix meng- which is a transitive verb, the use of the prefix di- which is a transitive passive verb, and the use of the prefix ber- which is a nontransitive verb. (2) It was found that two types of word classes were used in indicating the stylistic use of personification, namely: nouns and adjectives. Conclusions The word forms used to construct personified language styles in Joko Pinurbo's Srimenanti novel vary.